KONSTRUKSI BRANDING PRODUK MELALUI STRATEGI KOMUNIKASI PEMASARAN TERPADU PADA AKUN @melvantbali - Dinda Vania Zabrina Rachman; I Gusti Ayu Agung Dewi Sucitawathi Pinatih; Melati Budi Srikandi; I Wayan Joniarta (Bajang Institute, 2026)
This study aims to analyze the implementation of Integrated Marketing Communication (IMC) on the Instagram account @melvantbali in building brand image and strengthening product branding as a local streetwear-based fashion brand. This research employs a descriptive qualitative method and is grounded in the IMC framework proposed by Kotler and Keller, which consists of eight key elements of marketing communication: advertising, sales promotion, events and experiences, public relations and publicity, online and social media marketing, mobile marketing, direct and database marketing, and personal selling. The findings show that these communication elements operate in an integrated and consistent manner, creating message unity, visual identity continuity, and a strong brand experience in the minds of the audience. Advertising through visual content shapes brand identity, sales promotion is applied selectively without reducing brand exclusivity, events and experiences strengthen consumer trust through direct interaction, while public relations reinforces brand legitimacy and value through storytelling. Furthermore, online and social media marketing enable participatory two-way communication, mobile marketing fosters psychological closeness through real-time responses, direct and database marketing build personalized relationships with consumers, and digital personal selling functions as a supportive process in purchase decision-making. These findings indicate that IMC is not merely a promotional instrument, but a relational strategy that shapes emotional engagement, brand awareness, and consumer trust toward the brand.